Digital Adaptation Requirements for Preceptorship of Newly Graduated Nurses - Melati, Lina; Aini, Qurratul (Indonesian Journal of Innovation Studies, 2026)
General Background: Digital transformation in healthcare through Electronic Medical Records and hospital information systems requires nurses to possess advanced digital competencies alongside clinical skills. Specific Background: Newly graduated nurses experience transition shock intensified by simultaneous clinical responsibilities and digital system demands, while existing preceptorship programs remain predominantly clinically oriented and lack structured digital integration. Knowledge Gap: There is limited evidence on structured preceptorship models that systematically incorporate digital adaptation to address technostress, documentation errors, and competency gaps among novice nurses. Aims: This study aims to analyze the requirements for a digital adaptation-based preceptorship program for newly graduated nurses. Results: Using a descriptive qualitative case study with interviews and focus group discussions involving 18 stakeholders, three core needs were identified: a safe digital learning environment through training dummy systems, standardized digital literacy for preceptors as technology mentors, and integration of competency monitoring via digital logbooks with real-time feedback. Findings also reveal the emergence of digital transition shock, documentation delays, data entry errors, and mentoring inefficiencies linked to inadequate digital preparedness. Novelty: This study proposes a structured digital preceptorship framework integrating psychological safety, simulation-based learning, and competency tracking within clinical mentoring. Implications: The findings highlight the necessity of embedding digital adaptation into preceptorship curricula to reduce digital malpractice risks, support nurse well-being, and ensure continuity and safety of patient care in digitally integrated hospital systems. Highlights: Dual clinical and technological demands create significant psychological and operational burden during early professional transition. Simulation-based systems provide a safe environment to minimize technical errors and anxiety. Structured mentoring with competency tracking improves readiness within digital healthcare systems. Keywords: Digital Preceptorship, Transition Shock, Electronic Medical Records, New Nurses, Digital Adaptation